[ f(x) = \sum{i=0}^n \log \frac{xi}{1 - \mathbf{b}^T \mathbf{x}} - \frac{\mathbf{x}^T \mathbf{A} \mathbf{x}}{\mathbf{b}^T \mathbf{x}} \log \frac{1 + \mathbf{b}^T \mathbf{x}}{1 - \mathbf{b}^T \mathbf{x}} ]

[ f(x) = \sum{i=0}^n \log \frac{xi}{1 - \mathbf{b}^T \mathbf{x}} ]

[ f(x) = \sum{i=0}^n \frac{1 - \mathbf{b}^T \mathbf{x}}{xi} \left( \frac{x_i}{1 - \mathbf{b}^T \mathbf{x}}\right)' ]

[ f(x) = \sum{i=0}^n \frac{1 - \mathbf{b}^T \mathbf{x}}{xi} \left( \frac{x_i}{1 - \mathbf{b}^T \mathbf{x}}\right)' ]

Thursday, 4 June 2020 10:15 GMT